Handicraft Sector Schemes: A Growth Trend Analysis - J. Lekshmi and Nadia Sha (RESEARCH ESSENCE, 2014)
Handicrafts activity is predominantly carried out in the unorganized house hold sector. The artisans\manufactures are household members practicing handicrafts activity jointly at their residence, who if need arises, employ other handicraft artisans for work. In India as well as in many other regions of the world, handicrafts sector is identified as the second largest sector of rural employment after agriculture. The potential of the Handicraft industry has been underestimated as this sector can contribute a lot to our economy. Artisans belong to economically backward low wage system, irregularity of work, lack of technical knowhow and lack of design. This study is beneficial for the policy makers in chalking out suitable schemes and making changes in the present schemes to develop the handicraft industry as well as artisans.